Impaired Mitochondrial Function and Ubiquitin Proteasome System Activate α-Synuclein Aggregation in Zinc-Induced Neurotoxicity: Effect of Antioxidants - Singh, Garima; Mittra, Namrata; Singh, Chetna (Journal of molecular neuroscience, 2025)
Impairment in mitochondrial function and ubiquitin–proteasome system (UPS) and alpha-synuclein (α-Syn) aggregation are implicated in Zn-induced neurotoxicity. A link among these events leading to Zn-induced neurotoxicity is not yet properly deciphered. Therefore, the study intended to check the existence of a crosstalk between the mitochondria and UPS and its further link to α-Syn aggregation. The study also aimed to investigate the efficacy of tempol, a SOD mimetic and silymarin, a natural antioxidant, against Zn-induced alterations in animals and differentiated cells. Zn reduced the locomotor activity, dopamine content and tyrosine hydroxylase (TH) expression in the exposed animals. Zn augmented the levels of mitochondrial reactive oxygen species, α-Syn and protein-ubiquitin conjugates. Mitochondrial membrane potential, adenosine triphosphate (ATP) production, UPS-associated enzymatic activities and levels of UPS subunits (SUG-1 and β-5) were attenuated in Zn-exposed animals. While Zn augmented the expression of heat shock protein 110 (HSP110), peroxisome proliferator-activated receptor-gamma coactivator - 1 alpha (PGC-1α) and Parkin translocation, the mitochondrial PTEN-induced kinase-1 (PINK-1) level was attenuated. In addition to tempol and silymarin, a mitochondrial permeability transition pore inhibitor, cyclosporine A, also alleviated the Zn-induced changes in animals. Similar trends in a few parameters were also observed in the differentiated human neuroblastoma SH-SY-5Y cells. Besides, UPS inhibitor, MG132, enhanced Zn-induced UPS impairment, protein aggregation and mitochondrial dysfunction in differentiated cells. These results suggest that mitochondrial dysfunction triggers UPS impairment or vice versa that elevates α-Syn aggregation and consequent neuronal death. Furthermore, tempol and silymarin ameliorate the mitochondrial and UPS impairments and α-Syn aggregation thereby providing protection from Zn-induced neurotoxicity.